Mobile-assisted focus on forms in English for academic purposes instruction: Investigating the impacts on learning academic words - Xodabande, Ismail; Boroughani, Tahereh (Frontiers in Psychology, 2023)
Focus on forms (FonFs) is a pedagogical approach in Instructed Second Language Acquisition (ISLA) that emphasizes students’ conscious and direct attention to learning target language features in isolation and outside their meaningful context. FonFs has been employed extensively in foreign language vocabulary instruction, and earlier studies reported positive results for such interventions. The present study investigated mobile-assisted FonFs in the context of English for Academic Purposes (EAP) to address the vocabulary learning needs of Iranian EFL students and examined developments in receptive and productive knowledge of academic words. In doing so, the participants in the experimental learning condition (N = 22) were exposed to academic vocabulary using digital flashcards on their mobile phones, and those in the control group (N = 15) used word lists. The participants’ vocabulary knowledge was tested using different measures before and after the treatments, and the results were compared using multivariate analysis of variance (MANOVA). The findings indicated that mobile-assisted FonFs was effective in receptive and productive vocabulary learning, and the experimental group outperformed the control group in the post-tests. The effect size of the observed differences was also large; however, differences in productive aspects of academic vocabulary knowledge were associated with smaller learning effects for mobile-assisted FonFs. The study contributes to the growing body of knowledge on mobile-assisted language learning and highlights some implications for teaching academic vocabulary via mobile-assisted FonFs.